Reference for the six minutes’ walk test for children 4 to 10 years old - Fabian Vasquez; Gabriela Salazar; Sofia Vasquez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
Introduction: Physical activity is important for health. The six minutes’ walk test is a simple measurement; whose importance is that can be applied to healthy children and some sick subjects. Objective: To generate a reference for the six minutes’ walk test in children 4 to 10 years old. Methods: Cross-sectional study in a sample of 1420 boys and girls, aged four to ten years, attending public, subsidized and private schools in the commune of Santiago de Chile. The six-minute test was used to construct the percentile distribution of the six-minute walk test. Results: A table was generated with the percentile distribution for children aged 4 to 10 years according to age and nutritional status to have a reference for the six-minute walk test in this age group. Conclusion: This investigation provides a way to obtain a reference that can be used to follow up boys and girls of similar age and nutritional status, over time.